IMPLEMENTATION OF PROJECT BASED LEARNING (PJBL) MODEL ASSISTED BY ELECTRONIC MODULES TO INCREASE STUDENTS’ SCIENCE LITERACY SKILLS - Dwi Darmayani; Nurhayani H. Muhiddin; Sitti Saenab (Universitas Negeri Makassar, 2024)
The research aims to determine: 1) students’ science literacy skills before and after implementation Project Based Learning (PjBL) model assisted by electronic modules on biotechnology material. 2) The improvement science literacy skills after implementation PjBL model assisted by electronic modules. 3) Significant improvement in science literacy skills after implementation PjBL model assisted by electronic modules. This research is a pre-experimental with One Group Pretest-Posttest Design. The population was class IX SMPN 27 Makassar, the sample was selected using Purposive Sampling technique and selected class IX.2 totaling 32 samples. The instrument of multiple choice totaling 25 items. Data analysis using descriptive and inferential analysis, as for the results obtained: 1) the science literacy skills of students before the implementation of the PjBL model assisted by electronic modules had a score of 6.16 in the low category and after of a score of 12.00 in the medium category, 2) the science literacy skills of students after the implementation of the PjBL model increased with an N-Gain score of 0.39 in the medium category. 3) there is a significant increase. So it is concluded that the PjBL model assisted by electronic modules can improve students' science literacy skills.